SURGA KULINER PEDAS ! (STUDI KASUS PERANCANGAN BUKU KULINER NEGERI LOMBOK) - Putra, Sandi Justitia; Ramadhan, Ihsan (Visualita Jurnal Online Desain Komunikasi Visual, 2021)
West Nusa Tenggara is one of the provinces in the Unitary State of the Republic of Indonesia which has two large islands, namely Lombok Island and Sumbawa Island with a central government located in the city of Mataram. Lombok Island has a variety of traditional culinary and has its own uniqueness, for example is Ares which is made from young banana or kedebong banana. However, there is another problem behind the traditional culinary diversity on the island of Lombok, namely the lack of knowledge of young people about traditional culinary on the island of Lombok. The purpose of this service is to make a traditional culinary book that discusses the traditional culinary on the island of Lombok. This design uses design thinking method in order to get the right problem solving solution in designing the work. The traditional culinary book "Negeri Lombok" was composed with so many visual markers such as the songket keker motif and a variety of photography that displays the traditional culinary of Lombok so that readers more quickly recognize and understand the content delivered. to want to learn and preserve the traditional cuisine of the region.